ANALISIS LAPORAN KEUANGAN GUNA ALAT UKUR KINERJA KEUANGAN PADA PT. GLOBAL IMOO TELEKOMUNIKASI - Tengku Juhri Agustan; Utari Permata Sari (UNIVERSITAS DHARMAWANGSA, 2022)
In connection with the research background and the formulation of the problem, the purpose of this study, namely to determine and analyze the financial performance of PT. Global Imoo Telecommunications from 2016 to 2019. The data used in this study may not be directly used as a basis for making decisions by the authors who carried out the research, but by other institutions in need. So, the data that the author uses is qualitative. Qualitative data is data in the form of certain numbers or quantities that are definite in nature which are measured in a number or theory. The conclusion of this study shows the liquidity ratio (liquidity ratio), based on the current ratio (current ratio) PT. Global ImooTelecommunications is in good condition because it is able to pay off its current liabilities with current assets owned by the company. Solvency ratio (leverage ratio) In the ratio of debt to assets (Debt ratio to Assets) has decreased every year indicates that PT. Global ImooTelecommunications is in good condition, where the lower the debit or percentage ratio, the better the security level of the funds. Profitability ratio (profitability ratio), in the ratio of gross profit margin (Gross Profit Margin), this ratio has increased. Where the higher the gross profit margin ratio, the better the profitability ratio and PT. Global Imoo Telecommunication in healthy condition. Activity Ratio, Calculation Result of Assets Turn Over Ratio (Total Assets Turn Over) has decreased in percentage every year. This indicates PT. Global ImooTelecommunications is less effective in utilizing its total assets for sales.